Functional outcomes of displaced metastatic fractures of proximal femur: comparison between prosthetic replacement and intramedullary nailing - Wangjiraphan, Noppadol; Songpaiboon, Ukrit (International Journal of Research in Orthopaedics, 2024)
Background: Surgical treatments for proximal femur metastasis include prosthetic replacement (PR) and intramedullary nailing (IMN). Controversy persists regarding the most appropriate surgical option, and previous studies have mixed outcomes of patients with both displaced and impending fractures. This study aimed to assess the early functional outcomes in patients undergoing PR or IMN specifically for displaced metastatic fractures. Methods: A retrospective cohort study was conducted on patients with displaced metastatic proximal femur fractures treated surgically between January 2013 and March 2023. Patients with metastases confined to the femoral head or neck without trochanteric extension, which is not an indication for IMN, were excluded. Patients were divided into PR and IMN groups. Functional outcomes were assessed using the Musculoskeletal Tumor Society (MSTS) score at three months postoperatively. Results: Seventeen patients (10 females, 7 males; mean age 63.1±10.7 years) were treated with PR, and 31 patients (18 females, 13 males, mean age 61.4±11.3 years) were treated with IMN. Preoperative MSTS scores were similar between PR and IMN groups (3.8±2.6 vs. 2.9±1.6, p=0.179). Postoperatively, PR group had significantly higher MSTS scores (16.6±7.0 vs. 12.8±5.1, p=0.045), with better scores in function (p=0.028), supports (p=0.005), and walking (p=0.032). PR group had longer operative time (142 vs. 90 min) and greater blood loss (650 vs. 200 ml) compared to IMN group. Conclusions: Patients with displaced proximal femur fractures from metastatic lesions had significantly higher MSTS scores with PR than with IMN at three months postoperatively.